Model Pengelolaan Keuangan Zakat Berbasis Fungsi Manajemen untuk Meningkatkan Efektivitas Penghimpunan Dana - Budi Gautama Siregar; Romando Yusrat (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2026)
Zakat collection in Indonesia has continued to increase; however, its realization remains significantly below the country's estimated zakat potential. This study aims to analyze the implementation of management functions in zakat financial management and to develop a management function based zakat financial management model to improve the effectiveness of zakat collection at the National Amil Zakat Agency (BAZNAS) of Padangsidimpuan City. This study employed a qualitative approach using interviews, observations, and documentation as data collection techniques. The data were analyzed using the Miles and Huberman interactive model and supported by NVivo 12 Plus. The findings indicate that the integration of planning, organizing, actuating, and controlling strengthens transparent, accountable, and effective zakat financial governance, thereby enhancing muzakki trust and improving the effectiveness of zakat collection. This study proposes the Integrated Zakat Financial Management Model (IZFMM) as a conceptual framework that contributes to the development of Islamic Social Finance and provides practical guidance for zakat management institutions in strengthening governance and improving zakat collection performance